Entrepreneurship education and problem based learning - Reis, Carlos Francisco de Sousa (2014)
In this paper we draw on the concept of Entrepreneurship Education and describe the Budapest Agenda and its Progression Model for Initial Teacher Education. The concept of entrepreneurship and entrepreneurship education is discussed. We than sketch the origins of Problem-Based Learning (PBL), comparing it to the traditional paradigm of learning. A specific reference is made to creativity importance for education, broadly conceived and EE in particular. PBL features and process are presented in order to give a practical insight regarding its educational appliance. Finally we try to show PBL’s potential for fostering Creativity and supporting Entrepreneurship Education.